Current developments in the diagnosis and treatment of giant cell arteritis - Szekeres, Denes; Al Othman, Bayan (Frontiers in Medicine, 2022)
Giant cell arteritis is the most common vasculitis in adults above 50 years old. The disease is characterized by granulomatous inflammation of medium and large arteries, particularly the temporal artery, and is associated acutely with headache, claudication, and visual disturbances. Diagnosis of the disease is often complicated by its protean presentation and lack of consistently reliable testing. The utility of color doppler ultrasound at the point-of-care and FDG-PET in longitudinal evaluation remain under continued investigation. Novel techniques for risk assessment with Halo scoring and stratification through axillary vessel ultrasound are becoming commonplace. Mainstay treatment with glucocorticoids remains largely unchanged thought therapeutics continue to evolve with new biologic agents effectively targeting many components in the giant cell arteritis inflammatory cascade. Notwithstanding these developments, patients continue to have substantial rates of relapse and biologic agents have their own side effect profile. Trials are underway to answer questions about optimal diagnostic modality, regiment choice, and duration.